2020
DOI: 10.2147/copd.s280401
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ninjin’yoeito Ameliorates Skeletal Muscle Complications in COPD Model Mice by Upregulating Peroxisome Proliferator-Activated Receptor γ Coactivator-1α Expression</p>

Abstract: Purpose: Sarcopenia, the loss of skeletal muscle mass and strength, is a common systemic consequence of chronic obstructive pulmonary disease (COPD) and is correlated with higher mortality. Ninjin'yoeito (NYT) is a Japanese herbal medicine used to treat athrepsia and anorexia and is reported to ameliorate weight loss and muscular dysfunction. Recent studies have shown that its crude components upregulate the peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α)-related pathway, which is involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
(79 reference statements)
0
18
0
Order By: Relevance
“…NYT reportedly ameliorates cigarette smoke-induced alveolar damage as indicated by the destructive index; however, it does not affect the air space enlargement, as indicated by the mean linear intercept in a cigarette smoke-induced COPD mice model [8]. This report suggests that NYT has some favorable effects on the localized damage to the alveolar wall, including that on fibroblasts, and that NYT has no effects on other connective structures, such as elastic fibers [8]. However, this report did not investigate the type of cells and the mechanism by which NYT treatment ameliorates cigarette smoke-induced injury.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…NYT reportedly ameliorates cigarette smoke-induced alveolar damage as indicated by the destructive index; however, it does not affect the air space enlargement, as indicated by the mean linear intercept in a cigarette smoke-induced COPD mice model [8]. This report suggests that NYT has some favorable effects on the localized damage to the alveolar wall, including that on fibroblasts, and that NYT has no effects on other connective structures, such as elastic fibers [8]. However, this report did not investigate the type of cells and the mechanism by which NYT treatment ameliorates cigarette smoke-induced injury.…”
Section: Discussionmentioning
confidence: 89%
“…In an in vivo study, NYT could ameliorate cigarette smokeinduced alveolar damage, as indicated by the destructive index in a mouse model of cigarette smoke-induced COPD. Although this previous report did not investigate the mechanism of action of NYT on lung damage, the authors suggested that NYT has some favorable effects on localized damage to the alveolar wall, including that on fibroblasts [8]. In addition, NYT has also been reported to have radical scavenging activity in hepatocytes [9] and can ameliorate nitric oxide-mediated lung injury in a murine cytomegalovirus (MCMV)-infected model [10].…”
Section: Introductionmentioning
confidence: 99%
“…NYT reportedly ameliorates cigarette smoke-induced alveolar damage as indicated by the destructive index; however, it does not affect the air space enlargement, as indicated by the mean linear intercept in a cigarette smoke-induced COPD mice model. This report suggests that NYT has some favorable effects on the localized damage to the alveolar wall, including that on broblasts, and that NYT has no effects on other connective structures, such as elastic bers [8]. However, this report did not investigate the type of cells and the mechanism by which NYT treatment ameliorates cigarette smoke-induced lung injury.…”
Section: Discussionmentioning
confidence: 93%
“…In an in vivo study, NYT could ameliorate cigarette smoke-induced alveolar damage, as indicated by the destructive index in a mouse model of cigarette smoke-induced COPD. Although this previous report did not investigate the mechanism of action of NYT on lung damage, the authors suggested that NYT has some favorable effects on localized damage to the alveolar wall, including that on broblasts [8]. In addition, NYT has also been reported to have radical scavenging activity in hepatocytes [9] and can ameliorate nitric oxidemediated lung injury in a murine cytomegalovirus (MCMV)-infected model [10].…”
Section: Introductionmentioning
confidence: 99%
“…Our study has found some DE genes between NaHS treatment group and CS + LPS group, such as Psen1 , Ptgs2 , Mpo , and Slc23a2 , were involved in oxidative stress pathway, and Ppargc1a was upregulated by NaHS treatment. The protein encoded by Ppargc1a gene (also known as PGC-1 α in human) is peroxisome proliferator-activated receptor gamma coactivator 1 α (PGC-1 α ), as a transcriptional coactivator, it is an important regulator of energy metabolism [ 34 ], overexpressed PGC-1 α alleviates oxidative stress and decreases apoptotic cell death in endothelial cells [ 34 ], and upregulation of PGC-1 α is associated with reduction of oxidative stress and inflammation in diabetic myocardium [ 35 ] and attenuation of COPD in mice [ 36 ]. PGC-1 α is essential for the induction of ROS-detoxifying enzymes such as glutathione peroxidase and SOD2 under oxidative stress, PGC-1 α null mice were sensitive to oxidative stress [ 37 ]; PGC-1 α inhibited mitochondrial oxidative stress by facilitating Nrf2 binding to antioxidant response element promoter site and inducing SOD2 expression in sepsis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%